Orthodontic incisor retraction caused changes in the soft tissue chin area: a retrospective study - Wenxin Lu; Xu Zhang; Li Mei; Pengfei Wang; Jiarong He; Yu Li; Zhihe Zhao (BMC, 2020)
Abstract Background To investigate the area and morphological changes around the soft tissue chin after orthodontic incisor retraction. Methods Fifty-nine female adults with bimaxillary protrusion requiring extraction of four premolars were included in the study. Cephalograms were taken before (T0) and after (T1) orthodontic treatment. The soft tissue changes, including the area, thickness and morphology were measured. Paired-t tests were performed for statistical comparisons. Pearson correlation analyses and backward multivariate regression analyses were used to identify the relationship between the soft tissue changes and incisor retraction. Results Following the incisor retractions (5.35 ± 1.79 mm and 4.42 ± 1.62 mm for the upper and lower, respectively), there was a significant increase in the soft tissue thickness of L1c-LL (0.64 ± 1.67 mm, P = 0.025) and Pog-Pog' (0.44 ± 1.10 mm, P = 0.022), and a significant decrease in the soft tissue thickness of B-B' (1.21 ± 1.34 mm, P <  0.01). Changes in the area of soft tissue chin and lower lip were not statistically significant (P > 0.05). Pearson coefficient between the thickness changes of B-B' and the retraction of lower incisors was − 0.376. The multiple correlations between the soft tissue thickness changes and incisor retractions were Y = 1.02-0.42a + 0.42b for L1c-LL, and Y = 0.17-0.31b for B-B'. Conclusions The orthodontic incisor retraction could cause soft tissue thickness changes (i.e. an increase in L1c-LL and Pog-Pog' and a decrease in B-B') without area changes.